Encyclopedia of Multimedia Technology and Networking 2005
DOI: 10.4018/978-1-59140-561-0.ch059
|View full text |Cite
|
Sign up to set email alerts
|

Information Systems Strategic Alignment in Small Firms

Abstract: The concept of “alignment” or “fit” expresses an idea that the object of design—for example, an organization’s structure or its information systems (IS)—must match its context to be effective (Iivari, 1992). More recently, Luftman (2004) has taken this argument one step further and argued that a lack of alignment within an organization will limit the effectiveness of the organization’s business strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This model points out that: (1) HR processes of EORC are identified based upon the PCF, hence these are evaluated by questionnaire of APQC; (2) according to items based PCF, the importance of the processes is measured by samples, and (3) scores of performance and importance are analyzed by IPA and then the processes that have the weakest performance and the highest importance are prioritized to be improved [14][15]. Focusing on key metrics of APQC, calculation of KPIs in HCM processes of EORC were done.…”
Section: Data Collectingmentioning
confidence: 99%
“…This model points out that: (1) HR processes of EORC are identified based upon the PCF, hence these are evaluated by questionnaire of APQC; (2) according to items based PCF, the importance of the processes is measured by samples, and (3) scores of performance and importance are analyzed by IPA and then the processes that have the weakest performance and the highest importance are prioritized to be improved [14][15]. Focusing on key metrics of APQC, calculation of KPIs in HCM processes of EORC were done.…”
Section: Data Collectingmentioning
confidence: 99%
“…However practical and empirical considerations have given rise to the proposed model whereby strategic alignment is represented as an indicator of a construct. As indicated by Cumps et al (2008) and Chen and Tsou (2007), there does not appear to be a hard or fast rule in academic literature on how to precisely measure alignment, and particularly in small firms (Cragg and Todorova, 2005). Examples of studies that present strategic coalignment or similar abstract concepts (e.g.…”
Section: Fig 1 Conceptual Modelmentioning
confidence: 99%
“…From an academic perspective, Cragg and Todorova (2005) argue that previous research has indicated that what has been applicable for large firms cannot be made necessarily applicable to small firms. Various sources such as Packalen (2010), Korvela and Packalen (2010) and Sum et al (2004) even assert that the needs and support of micro-enterprises differ significantly from larger (albeit small) organisations in terms of for example, finance and resource availability.…”
Section: Introductionmentioning
confidence: 99%
“…Given the economic importance of these micro‐sized companies, it is vital that they innovate to ensure their survival, growth, and sustainability (Verhees & Meulenberg, ; Wolff & Pett, ). This is especially important because some authors argue that certain key drivers found in large, or even in medium‐sized and small, companies may not be applicable to micro‐sized companies (Cragg & Todorova, ; Rubio, Alonso‐Almeida, & Rodriguez‐Anton, ). Thus, ICTs may help micro‐sized companies to achieve better performance in their supply chain, given that small companies are less centralized and more flexible and reactive in their responses than large firms and may therefore have a better capacity to adapt to market requirements (Rogers, ).…”
Section: Introductionmentioning
confidence: 99%